Bóng phủ thuốc: Tiếp cận mới trong điều trị tái hẹp lại trong Stent - Nguyễn Minh Hùng; Phạm Mạnh Hùng (Tạp chí Tim mạch học Việt Nam, 2015)
Bóng phủ thuốc: Tiếp cận mới trong điều trị tái hẹp lại trong Stent